Distinguishing Visual Fatigue, Mental Workload and Acute Stress in Immersive Virtual Reality with Physiological Data: pre-test results - Souchet, Alexis D.; Xie, Weifei; Lourdeaux, Domitile (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Virtual Reality Induced Symptoms and Effects (VRISE) can arise. Experimental paradigms are heterogeneous to assess them, and var-ious factors can induce physiological variations. Therefore, we developed a Stroop task to study and distinguish VRISE. We use eye tracking, ECG, EDA, and VRSQ, NASA-TLX, and STAI-6 questionnaires. Pre-tests have been conducted with 6 subjects exposed to 4 experimental conditions: control, dual task, stressful, and stere-oscopy. Subjects report different subjective visual fatigue and mental workload but not stress between conditions. Several physiological features are different between conditions. A VRISE detector can be envisioned based on physiological data and questionnaires as an index.